PENGARUH KOMPENSASI, KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN RETENSI KARYAWAN SEBAGAI VARIABEL MEDIASI PADA PT. HUTAN SAWIT LESTARI UNIT I DI KOTAWARINGIN TIMUR, KAL-TENG - Laden Mering; Yunikewaty, Yunikewaty; Achmad Syamsudin (LPSDI Bina Patria, 2023)
Research in the field of HRM, to improve employee performance by analyzing compensation, competence and organizational culture. The research was conducted at PT. Hutan Sawit Lestari unit I in East Kotawaringin, Central Kalimantan. Performed on 108 employees with quantitative methods and distributing questionnaires, and analyzed with the PLS 3.0 program. The results show that of the ten hypotheses, only four are accepted or significant. The results of the analysis show that compensation and organizational culture have an effect on employee retention, then compensation and employee retention have a significant effect on employee performance. Compensation has a positive and significant effect on employee performance through employee retention as a mediating variable. This shows that in PT. HSL For Sustainable, compensation has a very large effect on performance, meaning that the better the compensation given, the better the employee's performance. Future research can examine organizational support variables